SOFTSKILL-BASED QUALITY DELOPMENT STRATEGY IN SMP IT AL-AFKARI BATANG KUIS - Mesiono Mesiono; Muhammad Walimsyah Sitorus; Hera Herviana; Ismail Ismail; Ibnu Hajar (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
This study aims to determine the strategy for developing the quality of graduates based on soft skills, which includes planning a strategy for developing the quality of graduates, organizing a strategy for developing the quality of graduates, implementing a strategy for developing the quality of graduates, and monitoring the strategy for developing quality graduates. This study uses a descriptive qualitative approach. Data collection techniques, data analysis and data validity testing using triangulation. On the other hand, school principals have carried out optimally related to, (1) planning softskill-based graduate quality development strategies, (2) organizing softskill-based graduate quality development strategies, (3) implementing softskill-based graduate quality development strategies, and monitoring graduate quality development strategies. based on soft skills at SMP IT Al-Afkari Batang Quiz.Keywords: Development Strategy, Graduate Quality, Softskill